Electromyographic analysis of masseter and temporal muscles, bite force, masticatory efficiency in medicated individuals with schizophrenia and mood disorders compared with healthy controls. (25th March 2014) - de Oliveira, R. H.; Hallak, J. E. C.; Siéssere, S.; de Sousa, L. G.; Semprini, M.; de Sena, M. F.; Osorio, F. de L.; Nunes, E. A.; Pinto, J. P.; Regalo, S. C. H.
Summary This study aimed to comparatively analyse the electromyographic activity of the masseter and temporal muscles at rest and during mandible postural clinical conditions (right and left laterality, protrusion and maximum voluntary contraction), right and left maximum molar bite forces and the masticatory efficiency of individuals with schizophrenia or mood disorders – all medicated (medicated groups) compared with control group (healthy volunteers) via electromyography. Individuals were distributed into three groups: Group I (Schizophrenia – 20 individuals), Group II (mood disorders – 20 individuals) and Group III (Control – 40 individuals). Basically, the results were only statistically significant for the clinical mandible conditions and bite force. The most unsatisfactory results were observed in the medicated groups in relation to the control group. The group with mood disorders obtained the most unsatisfactory results compared with the group with schizophrenia. It was suggested by these observations that the association of mood disorders and schizophrenia with medication has negatively affected the stomatognathic system in relation to controls when the electromyography and bite force were used for the analysis.